OS05.9.A Short-term fasting in glioma patients - Analysis of diet diaries and metabolic parameters of the ERGO2 trial. (9th September 2021) - Voss, M; Wenger, K J; von Mettenheim, N; Bojunga, J; Vetter, M; Diehl, B; Gerlach, R; Ronellenfitsch, M W; Franz, K; Harter, P N; Hattingen, E; Steinbach, J P; et al.
Abstract: BACKGROUND: The prospective, randomized ERGO2 trial investigated the effect of fasting / calorie restricted ketogenic diet (KD-IF) on re-irradiation for recurrent brain tumors (Clinicaltrials.gov number: NCT01754350). The study did not meet its primary endpoint of improved progression-free survival in comparison to a standard diet (SD). We here report the results of the quality of life questionnaire, neurocognition testing, detailed analysis of the diet diaries and the alterations of metabolic parameters. MATERIAL AND METHODS: 50 Patients were randomized 1:1 to re-irradiation combined with either SD or KD-IF. The KD-IF schedule included 3 days of ketogenic diet (KD: 21–23 kcal/kg/d, carbohydrate intake limited to 50 g/d), followed by 3 days of fasting and again 3 days of KD. Follow-up included examination of cognition, quality of life and serum samples. RESULTS: The 20 patients who completed KD-IF met the prespecified goals for calorie and carbohydrate restriction. In these, a decrease in leptin and insulin and an increase in uric acid was observed. The SD group had a lower calorie intake of 21 kcal/kg/d than the expected 30 kcal/kg/d. Neither quality of life nor cognition were affected by the diet. Low glucose emerged as a significant prognostic parameter in a best responder analysis. CONCLUSION: The strict caloric goals of the ERGO2 trial could be achieved by patients with recurrent brain tumor. The unexpected lower calorie intake of the SD group might have hampered the interpretation of the trial. However, the short diet schedule already led to significant metabolic alterations, suggesting that short-term dietary interventions might be therapeutically useful, possibly combined with other modalities.